Balance training programs for soccer injuries prevention - Gioftsidou, A. F.; Malliou, P.; Pafis, G.; Beneka, A.; Tsapralis, K.; Sofokleous, P.; Kouli, O.; Rokka, S.; Godolias, G. (Journal of Human Sport & Exercise, 2012)
The purpose of the study was to compare 2 different balance training programs, based on distinct exercise frequencies, with the aim of improving proprioceptive ability. Thirty eight professional soccer players, were randomly assigned into 3 groups: the A group, exercised with a frequency of 6 times per week, for 3 weeks, the B group exercised with a frequency of 3 times per week, for 6 weeks and the C group (control) did not follow a highly specific balance training, but only a standard soccer training. All participants were evaluated with the use of an electronic stability system (indices-deviations) and of a wooden balance board (time on balance) before (pre test) and after the training period (post test). Analyses of variance (ANOVAs), with repeated measures on the last factor, were conducted to determine effect of training programs and measures (pre-test, post-test) on balance test indices (SI, API, and MLI) and time on balance board. The results showed that both training groups improved their balance ability similarly (p<0.05) despite the different frequency of the balance training program. The authors proposed that balance training program can be applied in soccer players on a daily basis or at least 3 times per week, according to the demands of the training period.